Sociology and visual representation - Chaplin, Elizabeth 1939- (Routledge, 1994)
Our culture has become far more visual. Recent technological developments have engendered a transformation. Visual representation now concerns a wide spectrum of social scientists: no longer is it the province of a mere handful interested in visual art. This book is concerned with still images, diagrams, and the visual presentation of the written text. It is particularly aimed at postgraduate students, and provides a selective historical survey of texts whose authors have contributed to the development of the social analysis of visual representation. It focuses, especially, on those recent texts which have changed the relationship of analysis to topic by incorporating visual representation into the analysis itself.